The Role of Empathy in Leadership Ethics: Examining Empathic Relational Leadership Practice through Video-Based Methods - Nakamura, Yoshie Tomozumi (Business ethics quarterly, 2026)
Using a relational leadership lens, this study aims to gain a deeper understanding of empathic conversations with a focus on leadership ethics. It adopts an entitative perspective in relational leadership and examines leadership conversations as a two-way influence relationship, highlighting their interdependencies and collective role in the co-construction of meaning. Data from facial expression software and perception surveys are analyzed. The results of this study reveal the influence of gendered leadership on emotions, emotional bonding moments triggered by humor, and cultural dynamics in leadership conversations. Leaders' feeling-based questions and participants' willingness to share their emotions, coupled with emotion synchronization, create a constructive space where both feel invited, cared for, and valued. The study shows that emotional bonds foster the expression of generosity, care, and responsibility, enhancing satisfaction for both leaders and participants. Overall, this study enriches relational leadership theory and practice by underscoring the connection between empathy and leadership ethics.